Effect of Muscular Exercise on Patients With Muscular Dystrophy: A Systematic Review and Meta-Analysis of the Literature - Gianola, Silvia; Castellini, Greta; Pecoraro, Valentina; Monticone, Marco; Banfi, Giuseppe; Moja, Lorenzo (Frontiers in Neurology, 2020)
Background: Muscular dystrophy causes weakness and muscle loss. The effect of muscular exercise in these patients remains controversial. Objective: to assess the effects of muscular exercise versus no exercise in patients with muscular dystrophy. Methods: We performed a comprehensive systematic literature search in the Medline, Embase, Web of Science, Scopus, and Pedro electronic databases, as well as in the reference literature. We included randomized clinical trials (RCTs) that reported the effect of muscular exercise on muscle strength, endurance during walking, motor abilities, and fatigue. Data were extracted independently by two reviewers. Mean difference (MD) and 95% confidence intervals (CI) were used to quantify the effect associated with each outcome. We performed pairwise meta-analyses and trial sequential analyses (TSA) and used GRADE to rate the overall certainty of evidence. Results: We identified 13 RCTs involving 617 patients. The median duration of exercise interventions was 16 weeks (interquartile range [IQR] 12-24). In the patients with facio-scapulo-humeral dystrophy and myotonic dystrophy, no significant difference in extensor muscle strength was noted between the exercise and the control groups (4 studies, 115 patients, MD 4.34, 95% CI -4.20 to 12.88, I2=69%; p=0.32; minimal important difference [MID] 5.39 meters). Exercise was associated with improved endurance during walking (5 studies, 380 patients, MD 17.36 meters, 95% CI 10.91 to 23.81, I2=0; p<0.00001; MID 34 meters). TSA excluded random error as a cause of the findings for endurance during walking. Differences in fatigue and motor abilities were small. Not enough information was found for other types of dystrophy. Conclusions: Muscular exercise did not improve muscle strength and was associated with modest improvements in endurance during walking in patients with facio-scapulo-humeral and myotonic dystrophy. Future trials should explore which type of muscle exercise could lead to better improvements in muscle strength. PROSPERO: CRD42019127456